The Poetry of Hanshan (Cold Mountain), Shide, and Fenggan - Nugent, Christopher (Library of Chinese Humanities, 2016)
Due to their popularity with the American counterculture, the poems attributed to Hanshan, Shide and Fenggan have been translated several times in recent decades. However, previous translations have either been broadly popular in nature or have failed to understand fully the colloquial qualities of the originals. This new version provides a complete Chinese/English edition of the poems, aimed at combining readability with scholarly accuracy. It will prove useful to students of Chinese poetry and of Chinese religion, as well as anyone interested in a better understanding of works that have proved so influential in the history of East Asian Buddhism and in world literature.